En kulturanalytisk medieforskning - Arvidsson, Alf; Liliequist, Marianne (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1994)
In this issue of Kulturella Perspektiv we want to present some examples of media research with a more qualitative approach than the traditional mass communication research with its quantitative sociological orientation.